Association between the response to B cell depletion therapy and the allele*2 of the HS1,2A enhancer in seropositive rheumatoid arthritis patients Association between the response to B cell depletion therapy and the allele*2 of the HS1,2A enhancer in seropositive rheumatoid arthritis patients - D. Frezza; B. Tolusso; E. Serone; M.C. Totaro; S. Canestri; E. Gremese; G. Ferraccioli (PAGEPress Publications, 2012)
Objective. Several studies underline the relevance of the genetic background for the response to therapy. We evaluated the relationship between the polymorphism of the HS1,2A enhancer, located in the 3' regulatory region of the heavy immunoglobulin chain (IgH), and the response to B cell depletion therapy (BCDT) with Rituximab (RTX). Methods. Fifty rheumatoid arthritis (RA) patients (42 women; disease duration 13.9±10.6 years) treated with RTX, not responsive to previous DMARDs and/or TNFα inhibitors therapies, and 220 healthy subjects were enrolled in the study. Patients were genotyped for HS1,2A enhancer polymorphism, as previously described. Disease activity was assessed every three months according to the European League Against Rheumatism's (EULAR) criteria. Results. All RA patients were seropositive for at least one of the tested autoantibodies: rheumatoid factor (FR IgA, FR IgM e FR IgG), anti-cyclic citrullinated peptides (anti-CCP IgA, anti-CCP IgM e anti-CCP IgG) and anti-vimentin antibodies. RA patients had an increased frequency of the allele*2 (60.0%) of the HS1,2A enhancer compared to healthy subjects (42.0%; OR(95%ICs): 2.07 (1.33-3.22)). Patients with a good EULAR response at 6 months follow-up visit had an increased frequency of genotype 2/2 (47.1%) compared to poor-responders RA patients (genotype 2/2: 18.2%, OR(95%ICs): 4.00 (1.09-14.68)). All the patients with a good EULAR response had the allele*2, thus showing a possible association with the allele in this population. Conclusions. The presence of allele*2 seems to be related to a good response to BCDT with RTX in seropositive RA patients, thus highlighting the role of the HS1,2A enhancer in B cell maturation and class-switch recombination. Objective. Several studies underline the relevance of the genetic background for the response to therapy. We evaluated the relationship between the polymorphism of the HS1,2A enhancer, located in the 3' regulatory region of the heavy immunoglobulin chain (IgH), and the response to B cell depletion therapy (BCDT) with Rituximab (RTX). Methods. Fifty rheumatoid arthritis (RA) patients (42 women; disease duration 13.9±10.6 years) treated with RTX, not responsive to previous DMARDs and/or TNFα inhibitors therapies, and 220 healthy subjects were enrolled in the study. Patients were genotyped for HS1,2A enhancer polymorphism, as previously described. Disease activity was assessed every three months according to the European League Against Rheumatism's (EULAR) criteria. Results. All RA patients were seropositive for at least one of the tested autoantibodies: rheumatoid factor (FR IgA, FR IgM e FR IgG), anti-cyclic citrullinated peptides (anti-CCP IgA, anti-CCP IgM e anti-CCP IgG) and anti-vimentin antibodies. RA patients had an increased frequency of the allele*2 (60.0%) of the HS1,2A enhancer compared to healthy subjects (42.0%; OR(95%ICs): 2.07 (1.33-3.22)). Patients with a good EULAR response at 6 months follow-up visit had an increased frequency of genotype 2/2 (47.1%) compared to poor-responders RA patients (genotype 2/2: 18.2%, OR(95%ICs): 4.00 (1.09-14.68)). All the patients with a good EULAR response had the allele*2, thus showing a possible association with the allele in this population. Conclusions. The presence of allele*2 seems to be related to a good response to BCDT with RTX in seropositive RA patients, thus highlighting the role of the HS1,2A enhancer in B cell maturation and class-switch recombination.